Identifying the Consequences of Strategic Entrepreneurship in Sports Business - Adeleh Azimi Delarestaqi; Seyed Mohammad Hossein Razavi; Mohammad Reza Boroumand (The Society of Aging and Physical Activity (SAPA), 2017)
Background. This research aimed at identifying the consequences of strategic entrepreneurship in sports business. Objectives. The objective of the research is to identify the consequences of deployment of strategic entrepreneurship in sports business. Method. A qualitative research approach was employed. Data collection was done through interview as well as research background. The population included the entrepreneurship experts and instructors, business managers, and sport entrepreneurs. Sampling method utilized was snowball and the theoretical framework was defined following 21 interviews. Data analysis was conducted through three coding levels of open, axial, and selective in ATLAS.ti 5.2. Results. The indexes are as follows : value creation, wealth creation, development of life quality, sustainable job creation, uncertainty reduction, infrastructure improvement, positive individual consequences, entrepreneurship institutionalization, increasing tendency to sport, innovation development, achievement continuum, occupational process development, enjoy the opportunity, improvement of occupational spirit, customer centric, and leverage of management skills. Conclusion. Strategic management and entrepreneurship make changes through opportunity discovery in uncertain environments of business. Therefore, strategic entrepreneurship creates positive consequences for business especially those in sports.